Endoscopic ultrasonography evaluation for pancreatic cysts: Necessity or overkill?. Issue 4 (11th May 2017) - Pausawasdi, Nonthalee; Ratanachu‐ek, Thawee
Abstract : Incidental pancreatic cysts have become gradually more recognized in clinical practice as a result of increased use of transabdominal ultrasound, computed tomography (CT) and magnetic resonance imaging (MRI). These lesions consist of inflammatory cysts (pseudocysts) and pancreatic cystic neoplasms (PCN) which have been classified as benign, premalignant and malignant. The diagnosis and management strategy of incidentally discovered pancreatic cysts can be challenging as the majority of them are PCN and CT or MRI alone may not be sufficient to provide an accurate diagnosis. Endoscopic ultrasound (EUS)‐guided fine‐needle aspiration provides a method to obtain cyst fluid for analysis and the recently developed EUS‐based technology including contrast‐enhanced ultrasound, cystoscopy and needle‐based confocal laser endomicroscopy allows endosonographers to gain additional useful information. The current data suggest that EUS evaluation of pancreatic cysts offers some benefits especially in cases of inconclusive CT or MRI.